Programa lúdico “Palein” para desarrollar la inteligencia intrapersonal e interpersonal de las niñas de 1° grado de Educación Primaria de la I.E n° 81007 “Modelo”- Trujillo, 2017 - Alvarado Ramírez, Lesly Helen (2018)
The main objective of this research work is to demonstrate how the playful program "PALEIN" influences the development of intrapersonal and interpersonal intelligence of girls in the 1st grade of primary education of the I.E. N ° 81007 "Modelo" -Trujillo, 2017. The research design used was quasi-experimental and it was worked with a sample of 50 students, 25 belonged to the experimental group and 25 to the control group, using the facilities of the Educational Institution mentioned. The playful program "PALEIN" was aimed at developing intrapersonal intelligence in the dimensions of self-esteem, self-knowledge and self-discipline and interpersonal intelligence in the dimensions of empathy, participation, interaction and understanding. For data collection, the application of an evaluation form that was used as pretest and posttest to know the level of intrapersonal and interpersonal intelligence was used as an instrument. Finally, for the processing of the results, the statistical software program SPSS (version 21.0) was used, by means of the Student t test and after the application of the "PALEIN" play program to the experimental group and according to the posttest, the results obtained show that the students managed to significantly improve the level of their intrapersonal and interpersonal intelligence unlike the control group.